Digitalisasi Ruang Pameran: Potensi Media Sosial Sebagai Platform Pameran Karya Seni Rupa - Dimas Setyo (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to examine the role of social media in art exhibitions in Indonesia using a literature review method. Along with the development of digital technology, social media has become one of the main platforms for exhibiting works of art, providing opportunities for artists to interact directly with global audiences without the limitations of physical space. In the Indonesian context, social media plays an important role in introducing works of art to the wider community, both domestically and internationally. Based on an analysis of various relevant literature sources, the results of this study indicate that Instagram, WhatsApp, and Facebook are the most adaptive social media for art exhibitions in Indonesia. Instagram, with its strong visual features, provides an opportunity for artists to exhibit their artworks professionally, while WhatsApp offers more personal and direct interaction with the audience. Facebook, with its extensive users, allows art exhibitions to be more organized and reach a more diverse audience. These findings indicate the importance of choosing the right social media in optimizing the distribution and participation in art exhibitions in this digital era. This study contributes to the development of art exhibition management, especially in the digital context, which is increasingly becoming the main choice for many artists in Indonesia.